Facing Disruptive Changes With Informal Workplace Learning Strategies: The Experience of European Companies - Amenduni, Francesca; Ryymin, Essi; Maetoloa, Katja; Cattaneo, Alberto (Frontiers in Psychology, 2022)
Industries are currently experiencing several kinds of disruptive changes, including digital transformation and environmental and health emergencies. Despite intense discussion about disruptive changes in companies, the impact of such changes on workplace learning is still underexplored. In this study, we investigated the impact of disruptive changes on informal learning practices according to the perspectives of employers, employees, and adult educators. Informal learning was operationalised along a continuum between organised informal learning (led by an instructor and intentional) and everyday informal learning (led by contextual factors, accidental, and unintentional). 55 companies’ representatives (average age = 43.2 years; SD = 11) from three European countries (Finland, Switzerland, and Italy) and four industrial fields (bioeconomy, tourism, textile, and building sectors) were interviewed. The interviews were further triangulated with questionnaires collected by employees from the same companies (N = 141; average age = 40.2 years, SD = 17.8). Questionnaire data were used to collect detailed information on individual informal workplace learning (IWL) strategies and digital technologies adopted in organised informal learning. The interview data were analysed using qualitative content analysis. A coding scheme was developed with five macro-categories organised into 23 sub-categories. Occurrence and co-occurrence analysis were performed to identify which individual and organisational factors and approaches support most learning, according to interviewees. Interviewees reported the possibility of interacting with colleagues and being autonomous as the main sources of everyday informal learning processes. Employees from the same companies reported model learning, vicarious feedback, and applying someone’s own ideas as the most frequent IWL strategies. Organised informal learning was mainly based on knowledge transfer, which reflects passive cognitive engagement by employees. Specifically, digital technologies in organised informal learning were poorly used for supporting reflection, constructive processes, and collaborative knowledge construction. The results suggest that participants believed that higher forms of cognitive engagement are possible only within face-to-face organised informal training or in everyday informal learning. Possible explanations of the results and practical implications are discussed.